(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the art of gold embroidery and its role in decorating sewing items. Gold embroidery is a unique national craft, the art of embroidering fabric with gold and silver threads, as well as pearls, stones and other decorative elements. This technique gives dresses, curtains, bags and other fabric items an elegant and rich look. The article provides detailed information about the history, main methods and importance of gold embroidery in modern sewing.